A pleasant homeomorphism for conditional probability systems - Peter A. Streufert (The University of Western Ontario, Department of Economics, 2002)
Suppose that there are n states, each denoted by i 1,2,...n. This paper shows that the function [pi|E]i E → [Σj ≠ i pi|i, j] i is a homeomorphism from the set of conditional probability systems onto the convex hull of all permutations of the n-dimensional vector (0,1,2,...n-1).
Keywords: 330